Micelle-Forming Block Copolymers Tailored for Inhibition of P-gp-Mediated Multidrug Resistance: Structure to Activity Relationship - Braunová, Alena; Kaňa, Martin; Kudláčová, Júlia; Kostka, Libor; Bouček, Jan; Betka, Jan; Šírová, Milada; Etrych, Tomáš (Pharmaceutics, 2019)
Multidrug resistance (MDR) is often caused by the overexpression of efflux pumps, such as ABC transporters, in particular, P-glycoprotein (P-gp). Here, we investigate the di- and tri- block amphiphilic polymer systems based on polypropylene glycol (PPO) and copolymers of (N-(2-hydroxypropyl)methacrylamide) (PHPMA) as potential macromolecular inhibitors of P-gp, and concurrently, carriers of drugs, passively targeting solid tumors by the enhanced permeability and retention (EPR) effect. Interestingly, there were significant differences between the effects of di- and tri- block polymer-based micelles, with the former being significantly more thermodynamically stable and showing much higher P-gp inhibition ability. The presence of Boc-protected hydrazide groups or the Boc-deprotection method did not affect the physico-chemical or biological properties of the block copolymers. Moreover, diblock polymer micelles could be loaded with free PPO containing 5-40 wt % of free PPO, which showed increased P-gp inhibition in comparison to the unloaded micelles. Loaded polymer micelles containing more than 20 wt % free PPO showed a significant increase in toxicity; thus, loaded diblock polymer micelles containing 5-15 wt % free PPO are potential candidates for in vitro and in vivo application as potent MDR inhibitors and drug carriers.
Keywords: block copolymers; solid tumors; P-glycoprotein; micelles; polymer therapeutics; multidrug resistance